The Role of Social Media in Increasing Brand Awareness: A Literature Review - Suparto, Yuyun Hadi (PT. Anagata Sembagi Education, 2024)
Social media has become an important platform in modern marketing strategies, especially in the context of increasing brand awareness. This research aims to investigate how social media can effectively increase brand awareness through visual content strategies, the use of influencers, and employee engagement. This research uses a literature review approach. This method aims to analyze and summarize existing ideas and knowledge related to the research topic and look for gaps for further research. This literature review is based on relevant academic sources, which can explain the latest thinking and identify theories related to the research. The results of the literature review show that social media is a very effective tool in building brand awareness in the current digital era. By using the right strategies, such as leveraging engaging visual content, collaborating with relevant influencers, and encouraging employee engagement in sharing company content, brands can reach a wider audience and increase brand recognition. The implications of this research emphasize the importance of companies adapting social media strategies that are responsive to changing trends and consumer preferences, so that they can maximize the influence of social media in strengthening brand image and achieving broader marketing goals.